Including fossils in phylogeny: a glimpse into the evolution of the superfamily Evanioidea (Hymenoptera: Apocrita) under tip-dating and the fossilized birth–death process. Issue 4 (13th July 2021) - Jouault, Corentin; Maréchal, Arthur; Condamine, Fabien L; Wang, Bo; Nel, André; Legendre, Frédéric; Perrichot, Vincent
Abstract: Using a fossilized birth–death model, a new phylogeny of the superfamily Evanioidea (including ensign wasps, nightshade wasps and hatchet wasps) is proposed, with estimates of divergence times for its constitutive families and for corroborating the monophyly of Evanioidea. Additionally, our Bayesian analyses demonstrate the monophyly of †Anomopterellidae, †Othniodellithidae, †Andreneliidae, Aulacidae, Gasteruptiida and Evaniidae, whereas †Praeaulacidae and †Baissidae appear to be paraphyletic. Vectevania vetula and Hyptiogastrites electrinus are transferred to Aulacidae. We estimate the divergence time of Evanioidea to be in the Late Triassic (~203 Mya). Additionally, three new othniodellithid wasps are described and figured from mid-Cretaceous Burmese amber as the new genus Keratodellitha, with three new species: Keratodellitha anubis sp. nov., Keratodellitha basilisci sp. nov. and Keratodellitha kirin sp. nov. We also document a temporal shift in relative species richness between Ichneumonoidea and Evanioidea.